PPE38 Protein of Mycobacterium tuberculosis Inhibits Macrophage MHC Class I Expression and Dampens CD8+ T Cell Responses - Meng, Lu; Tong, Jingfeng; Wang, Hui; Tao, Chengwu; Wang, Qinglan; Niu, Chen; Zhang, Xiaoming; Gao, Qian (Frontiers in Cellular and Infection Microbiology, 2017)
Suppression of CD8+ T cell activation is a critical mechanism used by Mycobacterium tuberculosis (MTB) to escape protective host immune responses. PPE38 belongs to the unique PPE family of MTB and in our previous study, PPE38 protein was speculated to participate in manipulating macrophage MHC class I pathway. To test this hypothesis, the function of mycobacterial PPE38 protein was assessed here using macrophage and mouse infection models. Decreased amount of MHC class I was observed on the surface of macrophages infected with PPE38-expressing mycobacteria. The transcript of genes encoding MHC class I was also inhibited by PPE38. After infection of C57BL/6 mice with Mycobacterium smegmatis expressing PPE38 (Msmeg-PPE38), decreased number of CD8+ T cells was found in spleen, liver, and lungs through immunohistochemical analysis, comparing to the control strain harboring empty vector (Msmeg-V). Consistently, flow cytometry assay showed that fewer effector/memory CD8+ T cells (CD44highCD62Llow) were activated in spleen from Msmeg-PPE38 infected mice. Moreover, Msmeg-PPE38 confers a growth advantage over Msmeg-V in C57BL/6 mice, indicating an effect of PPE38 to favor mycobacterial persistence in vivo. Overall, this study shows a unique biological function of PPE38 protein to facilitate mycobacteria to escape host immunity, and provides hints for TB vaccine development.